A model for measuring financial sustainability of local authorities: model development and application / Murugesh Arunachalam, Chen Chen and Howard Davey. - Arunachalam, Murugesh; Chen, Chen; Davey, Howard (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2017)
A key element of local government management accounting is an accountability system driven by benchmarks and techniques to evaluate the financial sustainability of local authorities. The accountability entails measuring the financial sustainability status of local authorities in a systematic way. Local authorities can use the results of the evaluation to streamline their operations to improve performance and set budgeting priorities. This study develops a model that measures and ranks the financial sustainability of local authorities. The model is then used to measure and evaluate the financial sustainability of two local authorities in New Zealand. The features of the model are: a set of financial and non-financial ratios; benchmarks for the ratios; a scoring and grading system; and a trend analysis technique. The study contributes to extant literature on model development for evaluating the financial sustainability of local authorities.